Shuttle walk tests in people with COPD who demonstrate exercise-induced oxygen desaturation: An analysis of test repeatability and cardiorespiratory responses. (May 2018) - McKeough, Zoe; Leung, Regina; Neo, Ji Hui; Jenkins, Sue; Holland, Anne; Hill, Kylie; Morris, Norman; Spencer, Lissa; Hill, Catherine; Lee, Annemarie; Seale, Helen; Cecins, Nola; et al.
Exercise-induced oxygen desaturation (EID) is prevalent in people with chronic obstructive pulmonary disease (COPD). This article reports a sub-analysis from a randomized controlled trial (RCT) in people with COPD and EID (COPD/EID). The primary aim, in people with COPD/ EID, was to determine the repeatability of the distance and time walked in the incremental shuttle walk test (ISWT) and endurance shuttle walk test (ESWT), respectively. A secondary aim was to determine whether any participant characteristics predicted those who did not demonstrate improvements on a repeat ISWT or ESWT. Participants with nadir oxygen saturation (SpO2 ) < 90% on the 6-minute walk test were recruited to the RCT. Two ISWTs and two ESWTs were then performed as part of the baseline assessments, and participants were included in this sub-analysis if their nadir SpO2 was <90% during the better of two ISWTs. Repeatability of the tests was analysed using Bland–Altman plots and paired t -tests. Participant characteristics of age, lung function, level of nadir SpO2 and end-test dyspnoea were used to predict those who were not likely to demonstrate improvements on a repeat test using receiver operating curves. Eighty-seven participants (mean age (standard deviation, SD) 70 (7) years; forced expiratory volume in one second (FEV1 ) 47 (17)% predicted) were included. The mean differences (coefficient of repeatability) for the ISWTs and ESWTs were 9 m (55 m) and 19 seconds (142 seconds) respectively ( p < 0.05). No participant characteristic predicted the absence of improvement on the second ISWT (area under the curve (AUC) ranged from 0.49 to 0.58, all p > 0.2) or the second ESWT (AUC ranged from 0.43 to 0.52, all p > 0.3). Although repeating the tests showed only small improvements in distance (ISWT) and time (ESWT) walked in people with COPD/EID, the variability was large making definite conclusions about test repeatability in these individuals difficult.